Unterrichtliche Nutzung digitaler Medien durch Lehrpersonen in der Sekundarstufe I im Bundesländervergleich und im Trend von 2015 bis 2017 - Lorenz, Ramona; Endberg, Manuela; Eickelmann, Birgit (Schule digital – der Länderindikator 2017. Schulische Medienbildung in der Sekundarstufe I mit besonderem Fokus auf MINT-Fächer im Bundesländervergleich und Trends von 2015 bis 2017)

Schule digital – der Länderindikator 2017. Schulische Medienbildung in der Sekundarstufe I mit besonderem Fokus auf MINT-Fächer im Bundesländervergleich und Trends von 2015 bis 2017

School-level predictors for the use of ICT in schools and students’ CIL in international comparison - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (Large-scale Assessments in Education)

Predictors of teachers’ use of ICT in school – the relevance of school characteristics, teachers’ attitudes and teacher collaboration - Drossel, Kerstin; Eickelmann, Birgit; Gerick, Julia (Education and Information Technologies)

ICT use in mathematics lessons and the mathematics achievement of secondary school students by international comparison: Which role do school level factors play? - Eickelmann, Birgit; Gerick, Julia; Koop, Christian (Education and Information Technologies)

Teachers‘ attitudes and beliefs regarding ICT in teaching and learning in European countries - Eickelmann, Birgit; Vennemann, Mario (European Educational Research Journal)
In the debate on the integration of information and communication technologies (ICT) into schools, the beliefs and attitudes of teachers towards ICT in teaching and learning have always been regarded as central criteria for successful implementation of new technologies. In this context, a study in 2013 by the International Association for the Evaluation of Educational Achievement, IEA, provided insights into teachers’ beliefs regarding ICT and showed that perceptions of the pedagogical advantages of technologies differ between countries. With regard to this finding, this paper seeks to determine whether there is a typology of teachers with different attitudes towards the potential of ICTs for learning. This question is addressed by conducting latent class analyses on a sample of teacher data from three European countries – the Czech Republic, Germany and Norway. Furthermore, the paper investigates how the use of computers by teachers varies between the groups to which these teachers can be assigned. In doing so the research reported at hand connects, arguably for the first time, representative data on teacher typologies of attitudes towards and beliefs about ICT in teaching and learning with data on computer use in schools.

The international computer and information literacy study from a European perspective: Introduction to the Special Issue - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (European Educational Research Journal)
The International Computer and Information Literacy Study (ICILS 2013) provides, for the first time, information about students’ computer and information literacy (CIL), as well as its acquisition, based on a computer-based test for students and background questionnaires. Among the 21 education systems that participated in ICILS 2013, there are 12 European countries, making secondary comparative in-depth analyses at a European level particularly fruitful. Accordingly, while the four articles in this Special Issue each deal with different topics and adopt different methodologies, they all share a common element and provide European comparisons in the ICILS context. The editorial in turn outlines the aim of the ICILS 2013 study and its relevance for European education research as well as its contextual framework and approach to the measurement of students’ CIL. The potential and challenges of such large-scale assessment studies are also discussed.

The Use of Tablets in Secondary Schools and Its Relationship with Computer Literacy - Drossel, Kerstin; Eickelmann, Birgit (Tomorrow's learning: involving everyone. Learning with and about technologies and computing)

Schulische Medienkompetenzförderung - Eickelmann, Birgit (Medienkompetenz. Herausforderung für Politik, politische Bildung und Medienbildung)

Понять, как они тикают [Verstehen, wie sie ticken]. Interview on CLIL conducted by Ирина Долженко [Irina Dolzhenko] on behalf of sib.fm - Dolzhenko, Irina; Rumlich, Dominik

Unter welchen Voraussetzungen kooperieren Grundschullehrkräfte im inklusiven Unterricht? Eine Studie zu den Bedingungen der Kooperationsbereitschaft von Grundschullehrerinnen und -lehrern im inklusiven Unterricht - Hellmich, Frank; Hoya, Fabian Karl; Görel, Gamze; Schwab, Susanne (Empirische Sonderpädagogik)
Als wichtige Bedingungen für die Realisierung inklusiven Unterrichts in der Grundschule gelten Kooperationen von Grund- und Sonderschullehrkräften. Bislang ist wenig darüber bekannt, unter welchen Voraussetzungen Grundschullehrkräfte Bereitschaft zur Kooperation im inklusiven Unterricht zeigen. Vor diesem Hintergrund haben wir 168 Grundschullehrkräfte einerseits zu ihrer Kooperationsbereitschaft im inklusiven Unterricht und andererseits zu ihren Einstellungen zur Inklusion und zur Teamarbeit, ihren Erfahrungen aus dem integrativen bzw. inklusiven Unterricht sowie ihren Selbstwirksamkeitsüberzeugungen für die Gestaltung des inklusiven Unterrichts befragt. Die Ergebnisse aus einem Strukturgleichungsmodell geben Hinweise auf die Bedeutungen der Einstellungen zur Teamarbeit und der Erfahrungen aus dem integrativen bzw. inklusiven Unterricht für die Kooperationsbereitschaft der Grundschullehrkräfte. (DIPF/Orig.)

Motivation für die Beschäftigung mit Inklusion während des Studiums bei Studierenden des Lehramts an Grundschulen - Hellmich, Frank; Görel, Gamze; Schwab, Susanne (Profession und Disziplin - Grundschulpädagogik im Diskurs)

Erfahrungen, Einstellungen und Motivation von Studierenden des Grundschullehramts in Hinblick auf den inklusiven Unterricht. - Görel, Gamze; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Self-efficacy of prospective Austrian and German primary school teachers regarding the implementation of inclusive education - Schwab, Susanne; Hellmich, Frank; Görel, Gamze (Journal of Research in Special Educational Needs)

Einstellungen von Kindern gegenüber Peers mit sonderpädagogischem Förderbedarf als Bedingungen der sozialen Partizipation im inklusiven Unterricht der Grundschule - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca (Inklusiver Unterricht in der Grundschule)

Primary school students’ implicit theories and their reading motivation. The role of parents’ and teachers’ effort feedback - Hellmich, Frank; Hoya, Fabian Karl (Zeitschrift für Psychologie)
Abstract. Parents’ and teachers’ effort feedback is considered to be an important prerequisite for children’s implicit theories of intelligence and their academic self-concepts as well as for their learning and achievement motivation. Therefore, our study examines whether differences in N = 685 primary school students’ implicit theories, their reading self-concepts, and their reading motivation can be predicted by their perceptions of their parents’ and teachers’ effort feedback on reading processes. The results of a structural equation model show that children’s perceptions of their parents’ effort feedback predict their implicit theories, their reading self-concepts, and their reading motivation. The correlation between children’s perceived parental effort feedback and their intrinsic reading motivation is mediated by their implicit theories. Children’s implicit theories and their reading motivation cannot be predicted by their perceptions of their teachers’ effort feedback.

Empirische Arbeit: Wahrgenommenes positives Feedback zu Leseprozessen in Elternhaus und Schule im Zusammenhang mit der Lesemotivation von Kindern im Grundschulalter - Hellmich, Frank; Hoya, Fabian Karl (Psychologie in Erziehung und Unterricht)

Soziale Selbstkonzepte von Kindern im Grundschulalter und ihre Einstellungen gegenüber Peers mit Förderbedarf in der sozial-emotionalen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Inklusiver Unterricht in der Grundschule

Decision Taking, Confidence and Risk Management in Banks from Early Modernity to the 20th Century